Party «clientelism» during the First Republic - the case of the Reconstituinte Party (1920-1923) - Gonçalves da Silva, João Manuel (1997)
There are some excellent studies of the cacique system during the period of liberalism in Portugal, but analyses of the respective party arrangements are scarce. In this article the author classifies and describes the various schemes of «clientelism» seen in the social and political relationships of a small party during the First Republic, and in its reproductive strategies. Furthermore, the author stresses the specific features, failures, and dysfunctional aspects of the «clientelist» parties, as well as the process, inherent in their activities, by which their legitimacy disappeared. There is a particular emphasis on the local pressures of the republican political system.